Relational foundations of an unequal consumer credit market: Symbiotic ties between banks and payday lenders. Issue 1 (14th December 2022) - Bea, Megan Doherty
Abstract: Banks have financially supported payday lenders for decades. In this article I qualitatively demonstrate how these financial relationships have reinforced and expanded a bifurcated consumer credit market, and why these relationships matter for consumer access to financial services. I use archival financial documents from publicly traded payday lending companies between 1996 and 2014, available through the Securities and Exchange Commission, to construct the bank‐payday lender network and reveal motivations for these financial relationships. I find that bank‐payday lender relationships are sustained over many years, and that these relationships are mutually beneficial, enabling payday lender expansion and providing a way for banks to quietly profit from high‐interest lending in the face of other regulatory constraints. Further, I show that these relationships have significantly reshaped the consumer credit market over the past two decades. I conclude by considering broader implications of symbiotic institutional relationships in contemporary markets.